Efficacy and safety of shensong yangxin capsules for persistent atrial fibrillation: a Systematic Review and meta-analysis of randomized controlled trials - Chen, Yifan; Wang, Liuding; Li, Yuying; A, Runa; OuYang, Jiahui; Jiang, Zhonghui; Gao, Zhuye (Frontiers in Pharmacology, 2025)
BackgroundShensong Yangxin (SSYX), a standardized Chinese preparation, is widely utilized in arrhythmia treatment. This research sought to assess the clinical advantages of SSYX for persistent atrial fibrillation (PsAF).MethodsWe searched seven databases and two registries to identify randomized controlled trials (RCTs) assessing SSYX as an adjunctive treatment for PsAF. We assessed methodological quality with the Cochrane Risk of Bias Tool 2.0, and conducted meta-analyses with RevMan 5.4.ResultsThe meta-analysis incorporated ten RCTs enrolling 1,713 patients with PsAF. SSYX combined with conventional treatments (CTs) significantly lowered the recurrence of AF compared to CTs alone (risk ratio [RR] = 0.65, 95% conffdence interval [CI] 0.56 to 0.75, P < 0.001). The results also showed that SSYX contributed to the reduction of left atrial diameter (MD = −1.41, 95% CI -2.48 to −0.34, P < 0.001) and P-wave dispersion (MD = −10.37, 95% CI -17.23 to −3.5, P = 0.003). Safety analysis revealed that the combination of SSYX and CTs decreased adverse reaction incidence (RR = 0.54, 95% CI 0.32 to 0.90, P = 0.02). The certainty of evidence was graded as moderate to low.ConclusionSSYX showed potential in preventing AF recurrence in PsAF patients. Nevertheless, these preliminary findings require validation through more rigorously designed trials, given methodological limitations impacting evidence certainty.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251008974, identifier CRD420251008974.